2016
DOI: 10.5014/ajot.2016.70s1-po6058
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Information Mothers Receive About Children's Picky Eating Habits: A Mixed-Methods Study

Abstract: Date Presented 4/9/2016 This mixed-methods study investigated how mothers of picky eaters perceive mealtime and obtain information about picky eating. Results suggest occupational therapists should use online sources and collaborate with pediatricians to communicate with parents about mealtime concerns. Primary Author and Speaker: Elizabeth Curney Additional Author and Speaker: Kimberly Wilkinson

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Increasingly, parents, particularly mothers, are utilising online mediums for parenting information, advice and social support (Moon et al, 2019). A recent study which recruited mothers through a parenting Facebook group identified that online forums were consulted for fussy eating information and support almost as often as health professionals (Curney & Wilkinson, 2016). An exploration of the fussy eating concerns parents' report online may capture broader perspectives of common feeding concerns while minimising social desirability bias.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, parents, particularly mothers, are utilising online mediums for parenting information, advice and social support (Moon et al, 2019). A recent study which recruited mothers through a parenting Facebook group identified that online forums were consulted for fussy eating information and support almost as often as health professionals (Curney & Wilkinson, 2016). An exploration of the fussy eating concerns parents' report online may capture broader perspectives of common feeding concerns while minimising social desirability bias.…”
Section: Introductionmentioning
confidence: 99%